2018
DOI: 10.1039/c7sm02145c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometrical parameters on rebound of impacting droplets on leaky superhydrophobic meshes

Abstract: When a droplet impacts a superhydrophobic sieve, a part of the droplet penetrates through it when the dynamic pressure (ρU) of the impinging droplet exceeds the breakthrough pressure (γΓ/A). At higher impact velocities, the ejected-jet breaks and separates from the main droplet. The remaining part of the droplet bounces off the surface showing different modes (normal bouncing as a vertically elongated drop or pancake bouncing). In this work, we have studied the effect of different geometrical parameters of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 36 publications
4
65
0
Order By: Relevance
“…Droplet impact was recorded at 64 000 frames per second, a frame rate at least 3 times faster than previous relevant experiments. 15,16,38 The exposure time was 10.0 ms for all experiments. Images were then analysed in ImageJ and Matlab.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Droplet impact was recorded at 64 000 frames per second, a frame rate at least 3 times faster than previous relevant experiments. 15,16,38 The exposure time was 10.0 ms for all experiments. Images were then analysed in ImageJ and Matlab.…”
Section: Methodsmentioning
confidence: 99%
“…15 In the extreme penetration case, most of the droplet volume shoots out of the pores and forms liquid 'slugs' extending from the opposite surface of the mesh. A further study demonstrated that superhydrophobic meshes 16 could effectively resist incoming droplets and eliminate protrusion. Droplet penetration in a superhydrophobic mesh is suppressed at a critical recoil velocity v r B (s/D) 1/6 (sG/A) 1/3 , indicating that penetration cannot be achieved by surface wettability alone.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations